Identity and violence in Ukraine: Societal developments since the Maidan protests - Steffen Halling; Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2015)
Since the Maidan protests erupted at the end of 2013 Ukrainian society has witnessed a deep transformation, in which polarising as well as consolidating tendencies can be identified. The "Revolution of Dignity" and Russia's violation of the country's territorial integrity have strengthened Ukrainian identity in a way that has enhanced social cohesion. But these developments and the accompanying violence have at the same time heightened pre-existing conflicts. Only a lasting stabilisation can prevent these social fractures from widening yet further. To that end Ukrainian and external actors will need to engage in processes of conflict management and social reconciliation. (SWP Comments)
Keywords: 320